CHALLENGES AND OPPORTUNITIES FOR SOCIAL SERVICES IN THE REPUBLIC OF BULGARIA (PANGEEA, 2025)
The paper focuses on the challenges and opportunities arising from the ongoing transformation of the social services in the Republic of Bulgaria. Bringing the services into an independent law and creating new structures in the social system are aimed at improving the quality of care and putting the user in an active role in the helping process. For the purpose of the study, a literature review on the current issues was conducted, publicly available data in the social assistance structure was analysed and interviews were conducted with social service providers who shared the challenges and opportunities they have identified from their practice. Several key areas are highlighted, which include legislation and staffing of the sector, etc.
Keywords: Republic of Bulgaria; Social Services; Reform